2022
DOI: 10.1039/d2ce00452f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assemblies of Zn(ii) complexes with a D–π–A ligand for sensing specific organic molecules

Abstract: It is attractive but challenging to develop effective fluorescent sensors for detecting specific organic compound. In this study, we designed and synthesized three Zn(II) complexes [Zn(3N3PY)2](NO3)2·3.5CH3OH (1), [Zn(3N3PY)(BIN)]·1.5DMF (2) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Nowadays, it attracts great attention with relation to the healthy and environmental issue such as detecting specific species and degrading harmful pollutants [ 1 , 2 ]. The detection of definite harmful species such as nitroaromatic compounds (NACs), ketone molecules, halogen flame retardants and so on have been extensively explored, however, the study on sensing biomolecules like amino acids (AAs) is limited [ 3 , 4 , 5 , 6 ]. It is known that AAs play key role in varied physiological activities [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it attracts great attention with relation to the healthy and environmental issue such as detecting specific species and degrading harmful pollutants [ 1 , 2 ]. The detection of definite harmful species such as nitroaromatic compounds (NACs), ketone molecules, halogen flame retardants and so on have been extensively explored, however, the study on sensing biomolecules like amino acids (AAs) is limited [ 3 , 4 , 5 , 6 ]. It is known that AAs play key role in varied physiological activities [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence quenching may be caused by two possible reasons: (1) the electron transfer from the excited state of sensor to the AN and (2) the resonance energy transfer from the sensor to the AN. 35 37 The addition of other analytes had almost no effect on the fluorescence intensity of SNUT-6 (Figure 6). Subsequently, the fluorescence responses of SNUT-6 as a function of AN concentration were quantitatively studied.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%